Alterations in peripheral blood immune cell profiles of neuromyelitis optica spectrum disorder across different phases and after B cell depletion therapy - Wang, Xuying; Guo, Ruoyi; Yao, Zhichao; Liu, Lu; Jia, Zhen; Song, Xiujuan; Li, Bin (Frontiers in Immunology, 2025)
IntroductionPeripheral blood immune cell profiles of neuromyelitis optica spectrum disorder (NMOSD) are still unclear under different disease states and after B cell depletion therapy. Moreover, NMOSD is often confused with multiple sclerosis (MS) and myelin oligodendrocyte glycoprotein antibody disease (MOGAD). The study aims to illustrate peripheral blood immune cell profiles of NMOSD under different disease states, after B cell depletion therapy, and compared with MS and MOGAD.MethodsThis study included 76 NMOSD patients, 20 MS patients, and 12 MOGAD patients in the acute phase, along with 37 controls whose sex and age were matched with NMOSD patients. Forty-two of 76 patients with acute NMOSD were followed in remission, of whom 13, 15, and 11 patients received rituximab treatment, inebilizumab treatment, or conventional immunosuppressive therapies alone, respectively. The levels of diverse peripheral blood immune cells were measured by blood routine examination and flow cytometry. Distinctions among groups were analyzed using statistical methods.ResultsCompared with controls and NMOSD patients in remission, there was an elevation in the levels of neutrophils, platelets, platelet/lymphocyte ratio, neutrophil/lymphocyte ratio, and systemic inflammation index in acute NMOSD patients, while a decline was observed in the levels of lymphocytes, eosinophils, basophils, CD3+ T cells, CD3+CD4+ T cells, and CD4/CD8 ratio. NMOSD had increased levels of platelets and platelet/lymphocyte ratio, and decreased levels of eosinophils, basophils, CD4/CD8 ratio, and CD3+CD4+ T cells compared with MS. NMOSD had decreased levels of eosinophils, basophils, and CD19+ B cells, along with elevated platelet/lymphocyte ratio compared with MOGAD. After rituximab treatment, not only did CD19+ B cell level decrease, but eosinophil counts also increased. After inebilizumab treatment, not only did CD19+ B cell level decrease, but also the ratios of CD3+ T cells and CD3+CD8+ T cells increased. The quantity and ratios of eosinophils in rituximab group surpassed those in inebilizumab group.DiscussionPeripheral blood immune cell profiles of acute NMOSD patients showed widespread distinctions compared to those of remission NMOSD patients, acute MS patients, acute MOGAD patients, and controls, as well as after differential therapies. Our findings provide clues to comprehensively understand the abnormality of the dynamic and integrated immune network in NMOSD, distinguish NMOSD from MS and MOGAD, and search for more effective and safe therapeutic targets.